2015 International Conference on Unmanned Aircraft Systems (ICUAS) 2015
DOI: 10.1109/icuas.2015.7152306
|View full text |Cite
|
Sign up to set email alerts
|

Quadrotor control in a wind field

Abstract: This paper investigates the ability of a quadrotor to maneuver in a wind field. A dynamic model of a quadrotor is presented to model its motion. The quadrotor model includes a wind effect model to quantify the effect of wind on the dynamics of a quadrotor. A proportional-integral-derivative (PID) controller is shown as a baseline controller typically used on quadrotors. A LQR controller is then shown as an alternative to a PID controller. These two controllers are compared in a simulation environment using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 8 publications
0
28
0
Order By: Relevance
“…The temporal frequency f ω is given by (22). The relation between spatial frequency and angular frequency is described by (23). The relation in (23) is substituted in each of the PSD functions S a−w (f ), S c−w (f ), S v−w (f ) and the result is divided by B u to derive the PSD functions in terms of the temporal frequency S a−w (f ω ), S c−w (f ω ), S v−w (f ω ) as expressed in (24).…”
Section: Appendix Dryden and Von Karman Modelsmentioning
confidence: 99%
“…The temporal frequency f ω is given by (22). The relation between spatial frequency and angular frequency is described by (23). The relation in (23) is substituted in each of the PSD functions S a−w (f ), S c−w (f ), S v−w (f ) and the result is divided by B u to derive the PSD functions in terms of the temporal frequency S a−w (f ω ), S c−w (f ω ), S v−w (f ω ) as expressed in (24).…”
Section: Appendix Dryden and Von Karman Modelsmentioning
confidence: 99%
“…Regardless, flight testing has also demonstrated that the high frequency of control inputs required in highly turbulent conditions can exceed even the capability of experienced pilots for both multirotor and fixed-wing UA (Loxton et al, 2008;. As a result, improvements in disturbance rejection strategies continue to be investigated (Sydney, Smyth, & Paley, 2013b;Szczublewski, 2012;Tran, Bulka, & Nahon, 2015;Yeo, Sydney, & Paley, 2016).…”
Section: Affect Of the Environment On Suasmentioning
confidence: 99%
“…The mean wind impacts multirotors both through frame drag (Chen, He, & Zhou, 2013;Sydney et al, 2013a) and by setting the angle of the flow approaching the propellers. The horizontal component of this flow into the spinning rotor disk creates a force and corresponding moments that most significantly impact a multirotor's motion (Tran et al, 2015). However, under identical flight conditions, translational accelerations of an unmanned helicopter have been found to be roughly half that of a fixed-wing UA with rotational accelerations less than one-third .…”
Section: Affect Of the Environment On Suasmentioning
confidence: 99%
“…Among the first approach, Sydney et al [12] carried out an estimation process of the wind effect on a quadrotor and used it to design a control law capable of countering its disturbances. The authors in [13] investigated the wind effect on a quadrotor model, and showed that it can be viewed as an oblique flow approaching the rotors based on the bladeelement momentum theory. Huan et al [14] took into account the aerodynamic effect by proposing a law of aggressive command for a quadrotor using the blade flapping approach.…”
Section: Introductionmentioning
confidence: 99%